Analysis and Prioritization of Beef Suppliers in Meatball Grinding MSMEs Using the Analytical Hierarchy Process (AHP) Method - Island Dwi Batama Gustyananda; Hery Irwan (Greenation Research & Yayasan Global Resarch National, 2026)
Analysis and Priority Determination of Beef Suppliers in a Meatball Grinding SME Using the Analytical Hierarchy Process (AHP) Method Competition in the food industry, including bakso (meatball) milling businesses, demands precise decision-making in selecting suppliers for the main raw material, namely meat. Improper supplier selection can negatively impact product quality, operational costs, and business sustainability. The Analytical Hierarchy Process (AHP) method is used in this study to determine the best meat supplier for a meatball milling business at Tiban Market Center. The Analytical Hierarchy Process (AHP) method is used to structure the multi-criteria selection problem hierarchically and conduct pairwise comparison assessments of various criteria, such as availability, price, quality, and delivery timeliness. Three meat suppliers were evaluated as alternatives. Data collection was carried out through interviews, pairwise comparison questionnaires, and observations. The Analytical Hierarchy Process (AHP) analysis results show that the most important criterion is quality (weight 46.58%), followed by Timeliness (27.71%), Price (16.11%), and Availability (9.60%). The consistency test (CR = 0.0146) indicates that the evaluation is valid. Supplier 2 (0.5614) was chosen as the best supplier due to superior quality, although its price was not the lowest. Supplier 2 outperformed Supplier 1 (0.4714) and Supplier 3 (0.2786), respectively. These results provide a data-driven recommendation for the bakso milling business to select the supplier that best aligns with product quality and customer satisfaction.